RHETORICAL AWARENESS AND JORDANIAN EFL STUDENTS’ EXPOSITORY WRITING - Stapa, Siti Hamin; Irtaimeh, Mohammad (European Scientific Journal, ESJ, 2012)
This research aimed to investigate the transfer of Arabic rhetorical features into English by Jordanian Arab EFL students. It looked for differences in the transfer of two rhetorical features in relation to their gender as well as it explores the effectiveness of raising the students’ awareness of the importance of rhetoric in writing – culturally and rhetorically. The subjects for this study were the second Secondary Graders in the scientific stream in two schools, one for boys and one for girls, in two districts in the Governorate of Amman. The students in Al-Lames school for girls wrote one composition in English and one composition in Arabic, and the students in Al-Shareef school wrote one composition in English and one composition in Arabic. The results of the study showed that the rhetorical features were transferred intensively from Arabic into English. The study provided explanation for the rhetorical transfer in terms of the students’ L1 and its culture. In addition, the results showed statistically significant differences in the use of the rhetorical features in relation to all of the variables investigated in this study, gender, and familiarity of rhetorical transfer. The results also showed that the treatment of raising the students’ awareness of the importance of rhetoric in FL writing and of the cultural, rhetorical, and linguistic differences between Arabic and English had significantly reduced the transfer of all the rhetorical features. On the basis of the results, pedagogical implications were provided.